2017
DOI: 10.22319/rmcp.v8i4.4197
|View full text |Cite
|
Sign up to set email alerts
|

Macro-mineral concentrations in soil and forage in three grassland sites at Zacatecas

Abstract: Mineral concentration in forage is an important factor for extensive livestock production. Therefore, a study was performed in order to evaluate the soil mineral contents and their relationships with forage mineral concentrations taking into account three grassland sites located at Zacatecas state, México. Soil organic matter (OM) content and pH as well as soil and forage contents of Ca, P, Mg, Na and K were estimated. Soil OM contents were not different (P>0.05) among sites averaging 2.99 %. Soil pH of site 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In other animals, meaningful relationships have been found between Ca/P ratios and Ca absorption, and Ca deficiencies in blood serum could limit nitrogen and P utilization (Li et al, 2022). Márquez-Madrid et al (2017) found low Ca levels in the soil and forages and attributed these results to the soil Ca, influencing the forage P content.…”
Section: Mineral Content In Blood Serum Of Lactating Ewesmentioning
confidence: 99%
“…In other animals, meaningful relationships have been found between Ca/P ratios and Ca absorption, and Ca deficiencies in blood serum could limit nitrogen and P utilization (Li et al, 2022). Márquez-Madrid et al (2017) found low Ca levels in the soil and forages and attributed these results to the soil Ca, influencing the forage P content.…”
Section: Mineral Content In Blood Serum Of Lactating Ewesmentioning
confidence: 99%